The Effect of Training Methods and Eye-Foot Coordination on the Soccer Shooting Ability - Firdaus, Muhammad; Sulaiman, Sulaiman; Rustiadi, Tri (Journal of Physical Education and Sports, 2021)
The problem is SSB Tunas Kaili U17 players in Palu the low shooting ability. The purpose of the study was to analyzed the effect of shooting practice methods used motion balls and stationary balls, effect of high and low eye-foot coordination, and interactions shooting practice methods and eye-foot coordination on soccer shooting accuracy. This study uses an experimental method with a 2x2 factorial design, the data analysis uses Analysis Of Variance at the significance level (α: 0.05). The population in this study were SSB Tunas Kaili U17 players in Palu City in 2021, total 32 players. The results of this study: 1) the stationary ball shooting exercise got a mean of 14,40 while the motion ball exercise was 12,40 with a value (p = 0.000 <0.05). 2) High eye-foot coordination obtained an average shooting of 14,10 while low-eye coordination obtained an average shooting of 13,00 with a value (p=0.005<0.05). 3) The stationary ball exercise method that has high eye-foot coordination has a shooting average of 15,80, while for low eye-foot coordination, it is obtained a mean of 13,00 ball movements that have high eye-foot coordination, the average shooting is 12,40, while the average eye-foot coordination is low. Shooting average is 10,80 with a value (p = 0.003> 0.05) The conclusion is that stationary ball training shooting is better than motion ball training shooting on players who have high eye-foot coordinationhave better accuracy than players who have low coordination.